2017
DOI: 10.1017/s0954394517000059
|View full text |Cite
|
Sign up to set email alerts
|

The role of contextual frequency in the articulation of initial /f/ in Modern Spanish: The same effect as in the reduction of Latin /f/?

Abstract: The acoustic energy of 996 tokens of word-initial /f/ in the speech of 38 speakers of Mexican Spanish was analyzed. The results suggest that the frequency with which words occur in phonological contexts favorable to reduction (Frequency in a Reducing Context or FRC) conditions the reduction of /f/, even after taking into account the immediate phonological context. Despite this, it is also found that the conditioning effect of FRC is less robust than the influence of the immediate phonological context, thus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Those authors discovered a significant correlation between rates of occurrence of initial-/f/ words after nonhigh vowels and rates of deletion in modern-day Spanish, and they argued for the preeminence of word's ratio of conditioning over token frequency. In another study of /f/ in Spanish, E. K. Brown and Alba (2017) found similar results in an analysis of word-initial /f/ in immigrant Mexican Spanish in California. Additionally, E. K. Brown (2020) studied the variable voicing of word-final /s/ in Spanish (e.g., lo[z] niños 'the children, the boys'), and found that words that occurred relatively often in the context for voicing (i.e., before a voiced consonant) showed higher rates of voicing than other words.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Those authors discovered a significant correlation between rates of occurrence of initial-/f/ words after nonhigh vowels and rates of deletion in modern-day Spanish, and they argued for the preeminence of word's ratio of conditioning over token frequency. In another study of /f/ in Spanish, E. K. Brown and Alba (2017) found similar results in an analysis of word-initial /f/ in immigrant Mexican Spanish in California. Additionally, E. K. Brown (2020) studied the variable voicing of word-final /s/ in Spanish (e.g., lo[z] niños 'the children, the boys'), and found that words that occurred relatively often in the context for voicing (i.e., before a voiced consonant) showed higher rates of voicing than other words.…”
supporting
confidence: 60%
“…2.This variable has various names in the literature, among them the following: Frequency in a Favorable Context (or FFC; E. K. Brown, 2009; E. L. Brown, 2004), discourse context frequency (E. L. Brown, 2015), Frequency in a Reducing Context (E. K. Brown & Alba, 2017), Frequency of use in a Reducing Context (E. L. Brown, 2018), and contextual ratio frequency (E. K. Brown, 2018). …”
Section: Notesmentioning
confidence: 99%
“…This result falls in line what has been reported by other authors with respect to the interactive effect of FRC and the phonological context upon which it is based. Brown and Alba (2017) show that the effect of FRC interacts with the propitious phonological context for fricational reduction of word-initial /f/ in Spanish, as measured by the center of gravity of /f/. In that study, the influence of FRC was assuaged when measured in the conditioning context.…”
Section: Discussionmentioning
confidence: 77%
“…Brown (2018) shows that the conditioning effect of FRC also significantly interacts with the phonological context upon which it is based in an analysis of the duration and center of gravity of /s/ in Spanish, such that the effect of FRC is enlarged when measured in the conditioning context. Future studies will do well to continue exploring the interaction between FRC and the phonological context upon which it is based, and especially the magnifying effect that the favorable phonological context has on FRC's conditioning effect on the response variable in question in some studies (e.g., Brown 2018), while having an inhibitory effect with other variables (e.g., Brown and Alba 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The conditioning effects that accrue on words in memory can affect pronunciation variation (Brown, 2004(Brown, , 2020Brown & Alba, 2017;Chevrot et al, 2009), but FRC effects are also evident in morphosyntactic variation. Brown and Rivas (2012), for instance, examine variable regularization of the Spanish presentational verb haber ('there is / there are') with plural noun phrase (NP) complements and find that the rate at which haber pluralizes reflects each NP's likelihood of occurring as a grammatical subject.…”
Section: Forms' Ratio Of Conditioningmentioning
confidence: 99%